A Comparative Analysis of Attitudes Towards Women as Managers in the U.S. and Netherlands (Journal of Leadership, Accountability and Ethics, 2017)
This paper examines attitudes towards women as managers in a sample (n=166) of U.S. and Dutch male and female undergraduate business students using the women as managers scale (WAMS). Across both cultures, three factors emerged from the WAMS and were labeled “ability,” “acceptance,” and “female specific barriers.” Results showed that females held more favorable attitudes towards women as managers than did males. Similarly, but contrary to expectations, U.S. participants held more favorable attitudes towards women as managers than did Dutch participants. These results can inform both women managers and multinational corporations interested in improving the success of their international assignments.
Keywords: Leadership; Ethics; WAMS; Managers